Treatment of chemical synthesis-based pharmaceutical wastewater in an ozonation-anaerobic membrane bioreactor (AnMBR) system - Kaya, Yasemin; Bacaksiz, A. Murat; Bayrak, Hasan; Gonder, Z. Beril; Vergili, Ilda; Hasar, Halil; Yilmaz, Gulsum (Elsevier Science Sa, 2017)
In this study, treatability of etodolac chemical synthesis wastewater from the pharmaceutical industry was investigated in a hybrid ozonation-Anaerobic Membrane Bioreactor (AnMBR) system. The AnMBR was successfully operated up to 7500 mg/L of chemical oxygen demand (COD), but sulfite inhibition occurred at this loading. A pre-ozonation process was applied to overcome the problem of sulfite inhibition resulted from raw wastewater by decreasing the sulfite concentration through oxidation to sulphate. Furthermore, it was shown that this process was also effective obtaining high etodolac removal efficiencies up to 99%. Approximately 90% COD removal efficiency was achieved by the combined system. Extracellular polymeric substance (EPS) decreased in the conditions of long sludge retention time (SRT), hydraulic retention time (HRT) and low organic loading rate (OLR) values. Therefore, the granule size also decreased during the entire operation. Real-time polymerase chain reaction (Q-PCR) and fluorescent in situ hybridization (FISH) analyses revealed that high sulfite concentration affected the microbial population in the order of methanogens, acedogens and sulphate reducing bacteria (SRB). (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Anaerobic membrane bioreactor; Ozonation; Pharmaceutical wastewater; Microbial community